2013
DOI: 10.3168/jds.2013-7084
|View full text |Cite
|
Sign up to set email alerts
|

Variation in nutrients formulated and nutrients supplied on 5 California dairies

Abstract: Computer models used in ration formulation assume that nutrients supplied by a ration formulation are the same as the nutrients presented in front of the cow in the final ration. Deviations in nutrients due to feed management effects such as dry matter changes (i.e., rain), loading, mixing, and delivery errors are assumed to not affect delivery of nutrients to the cow and her resulting milk production. To estimate how feed management affects nutrients supplied to the cow and milk production, and determine if n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…It has been reported that dayto-day variability in nutrient composition was not as large as the variability observed between the fed and formulated recipe (Sova et al, 2014). The observed variability in TMR nutrient composition might have implications in regard to milk yield (Rossow and Aly, 2013;Sova et al, 2014). Due to these uncertainties associated with the feeding process, nutrition consultants often times add a safety margin by formulating rations that exceed requirements for critical nutrients such as CP.…”
Section: Introductionmentioning
confidence: 84%
“…It has been reported that dayto-day variability in nutrient composition was not as large as the variability observed between the fed and formulated recipe (Sova et al, 2014). The observed variability in TMR nutrient composition might have implications in regard to milk yield (Rossow and Aly, 2013;Sova et al, 2014). Due to these uncertainties associated with the feeding process, nutrition consultants often times add a safety margin by formulating rations that exceed requirements for critical nutrients such as CP.…”
Section: Introductionmentioning
confidence: 84%
“…Two scenarios were considered for data collection. Model 1 was based on primary data from 5 commercial dairies located in Tulare and Kings Counties, California (Rossow and Aly, 2013), and these were used to determine the average milk production and composition for this model. The average milk production representing 2014 model 1 levels was 39.8 kg/d, with milk fat and protein percentages of 4 and 3.3%, respectively.…”
Section: Functional Unitmentioning
confidence: 99%
“…Two different diets with respective milk production were considered for 2014 using IPCC assessment report 5 characterization factors (AR5; IPCC, 2014). Model 1 was based on highproducing cows in Rossow and Aly (2013), whereas model 2 was the average cow based on CDFA cost of milk production reports from 2013 to 2015.…”
Section: Data Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…Faecal, diet and diet refusal samples used in the determination of DMI were collected over the last 4 days of the 28‐days dosing period. Diet samples were collected once daily and subsampled from three tubs set along the feed bunk during feed delivery (Rossow & Aly, ). Refusal samples were collected once daily before the a.m. feeding, and average diet sample compositions were corrected with average residual compositions.…”
Section: Methodsmentioning
confidence: 99%